Cellular surface plasmon resonance-based detection of anti-HPA-1a antibody glycosylation in fetal and neonatal alloimmune thrombocytopenia - Szittner, Zoltán; Bentlage, Arthur E. H.; Temming, A. Robin; Schmidt, David E.; Visser, Remco; Lissenberg-Thunnissen, Suzanne; Mok, Juk Yee; van Esch, Wim J. E.; Sonneveld, Myrthe E.; de Graaf, Erik L.; Wuhrer, Manfred; Porcelijn, Leendert; et al. (Frontiers in Immunology, 2023)
Fetal and neonatal alloimmune thrombocytopenia (FNAIT) can occur due to maternal IgG antibodies targeting platelet antigens, causing life-threatening bleeding in the neonate. However, disease manifests itself only in a fraction of pregnancies, most common for anti-HPA-1a antibodies. We found that core fucosylation in the IgG-Fc tail in particular is highly variable in anti-HPA-1a IgG, which strongly influences binding to leukocyte IgG-Fc receptors IIIa/b (FcγRIIIa/b). Currently, gold-standard IgG-glycoanalytics rely on complicated methods (e.g., mass-spectrometry (MS)) not suited for diagnostics for this purpose. Our aim was to provide a simplified method to quantify the biological activity of IgG antibodies targeting cells. We developed cellular surface plasmon resonance imaging (cSPRi) technique based on FcγRIII-binding to IgG-opsonized cells, and compared the results to MS. The strength of the platelet binding to FcγR was monitored under flow using both WT FcγRIIIa (sensitive to Fc-glycosylation status) and mutant FcγRIIIa-N162A (insensitive to Fc-glycosylation status). The quality of the anti-HPA-1a glycosylation was monitored as the ratio of binding signals from the WT versus FcγRIIIa-N162A, using glycoengineered recombinant anti-platelet HPA-1a as standards. The method was validated with 14366 plasma samples with known clinical outcome previously with anti-HPA-1a antibodies analyzed by MS, with known clinical outcome, were tested for validation of the method. The ratio of patient signal from the WT versus FcγRIIIa-N162A correlated with fucosylation of the HPA-1a antibodies measured by MS (r=-0.52). Significantly, FNAIT disease severity based on Buchanan bleeding score was discriminated similarly by MS and cSPRi. In conclusion, using IgG- receptors, in this case FcγRIIIa, can be equipped on SPR chips to yield quantitative and qualitative information of platelet-bound anti-HPA-1a antibodies. Using opsonized cells in this manner circumvents the need for purification of specific antibodies and laborious MS analysis to yield qualitative antibody traits such as IgG fucosylation, for which no clinical test is currently available.